Empirical analyses of volatility spillover from G5 stock markets to Karachi stock exchange - Waleed Jan; Khalil Jebran (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
This study made a pioneering attempt to investigate volatility spillover from G5 countries stock markets to Karachi Stock Exchange (KSE) considering weekly data from 5th January, 2004 to 30th December, 2013. The G5 countries included in this study are France, Germany, Japan, UK and US. Johansen and Juselius cointegration test was applied to explore long run relationship between KSE and G5 equity markets. The volatility spillover has been analyzed by GARCH (generalized autoregressive conditional heteroskedasticity) model. We found long run relationship of KSE with equity markets of Germany and United Kingdom. The GARCH (1, 1) model reveals significant volatility spillover effect from all G5 equity markets to KSE. Based on empirical results, we suggest that there are low diversification opportunities for investors in Pakistan.
Keywords: 330; KSE; volatility spillover; G5 stock markets; GARCH